PEMANFAATAN BIOPESTISIDA RAMAH LINGKUNGAN TERHADAP HAMA Leptocorisa acuta TANAMAN PADI SAWAH - Salaki, Ch. L.; Pelealu, Jantje (EUGENIA, 2015)
ABSTRACT Â  The research was conducted in the centre production area of rice plants which on North Minahasa District and laboratory tests conducted in Entomology and Plant Pests Laboratory on Pest and Disease Plant course of Sam Ratulangi University, Manado. This research took one year of research period. The results of testing the power to kill isolates of entomopathogenic fungal isolates obtained the highest is MMTTO which had ability to kill nymphs of Leptocorisa acuta (93.3%). Followed by MMITO isolates (86.7%) and MMSAM (80.0%). The isolates are isolates of the fungus Metarhizium anisopliae. Selection results isolates of B. bassiana in nymphs L. acuta which best is BEMSAM isolates (86.7%) followed BEMTTO isolates (83.3%). Then those isolates will be used for the manufacture of biopesticide. Pathogenicity test results showed that each of entomopathogenic fungi to insects L. acuta after 7 days of infection, average mortality ranged from 83.3 to 93.3% and was significantly different from controls. Isolates Metarhizium sp and Beauveria sp each takes a minimum of 22.4 hours and 29.5 hours to kill 50% of test insects. Keywords : biopesticide, important pests, rice plant